Complementary SEM-AFM of Swelling Bi-Fe-O Film on HOPG Substrate - Sobola, Dinara; Ramazanov, Shihgasan; Konečný, Martin; Orudzhev, Farid; Kaspar, Pavel; Papež, Nikola; Knápek, Alexandr; Potoček, Michal (MDPI, 2020)
The objective of this work is to study the delamination of bismuth ferrite prepared by atomic layer deposition on highly oriented pyrolytic graphite (HOPG) substrate. The samples’ structures and compositions are provided by XPS, secondary ion mass spectrometry (SIMS) and Raman spectroscopy. The resulting films demonstrate buckling and delamination from the substrates. The composition inside the resulting bubbles is in a gaseous state. It contains the reaction products captured on the surface during the deposition of the film. The topography of Bi-Fe-O thin films was studied in vacuum and under atmospheric conditions using simultaneous SEM and atomic force microscopy (AFM). Besides complementary advanced imaging, a correlative SEM-AFM analysis provides the possibility of testing the mechanical properties by using a variation of pressure. In this work, the possibility of studying the surface tension of the thin films using a joint SEM-AFM analysis is shown.

The objective of this work is to study the delamination of bismuth ferrite prepared by atomic layer deposition on highly oriented pyrolytic graphite (HOPG) substrate. The samples’ structures and compositions are provided by XPS, secondary ion mass spectrometry (SIMS) and Raman spectroscopy. The resulting films demonstrate buckling and delamination from the substrates. The composition inside the resulting bubbles is in a gaseous state. It contains the reaction products captured on the surface during the deposition of the film. The topography of Bi-Fe-O thin films was studied in vacuum and under atmospheric conditions using simultaneous SEM and atomic force microscopy (AFM). Besides complementary advanced imaging, a correlative SEM-AFM analysis provides the possibility of testing the mechanical properties by using a variation of pressure. In this work, the possibility of studying the surface tension of the thin films using a joint SEM-AFM analysis is shown.
Complementary SEM-AFM of Swelling Bi-Fe-O Film on HOPG Substrate
Keywords: surface delamination; graphite substrate; atomic layer deposition; combined imaging; surface tension; surface delamination; graphite substrate; atomic layer deposition; combined imaging; surface tension